Pengaruh Reliabilitas, Perilaku Etis, Dan Kualitas Pelayanan Terhadap Loyalitas Nasabah di Mediasi Oleh Kepuasan - Bava Budiman; Muhammad Ridho (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Retaining customers means improving financial performance and maintaining the viability of the company. Therefore, banking companies will continue to strive to develop and improve their business in order to achieve company goals, one of which is by improving the quality of service to customers. This study aims to determine whether there is an influence of reliability, ethical behavior, and service quality on customer loyalty at BCA bank among bank customers. This study used a quantitative method by taking questionnaire data. The population in this study are relatives who use BCA. The results of this study indicate that reliability (X1), ethical behavior (X2), and service quality (X3) simultaneously have a positive and significant effect on customer loyalty (Y) in society, in saving savings at BCA